All together now: findings from a PCORI workshop to align patient-reported outcomes in the electronic health record. (November 2016) - Jensen, Roxanne E; Snyder, Claire F; Basch, Ethan; Frank, Lori; Wu, Albert W
In recent years, patient-reported outcomes have become increasingly collected and integrated into electronic health records. However, there are few cross-cutting recommendations and limited guidance available in this rapidly developing research area. Our goal is to report key findings from a 2013 Patient-Centered Outcomes Research Institute workshop on this topic and a summary of actions that followed from the workshop, and present resulting recommendations that address patient, clinical and research/quality improvement barriers to regular use. These findings provide actionable guidance across research and practice settings to promote and sustain widespread adoption of patient-reported outcomes across patient populations, healthcare settings and electronic health record systems.